An identified histaminergic neuron modulates feeding motor circuitry in Aplysia - Chiel, HJ (J Neurosci, 1986)
An identified histaminergic neuron, C2, in the marine mollusk Aplysia is a complex mechanoafferent which appears to contribute to the maintenance of food arousal by means of its synaptic connections to the metacerebral cell (MCC). Because C2 also has extensive synaptic outputs to neurons other than the MCC, we studied its possible motor functions. We identified several synaptic followers of C2 and found that some were excitatory motor neurons for extrinsic muscles of the buccal mass, while others were modulatory motor neurons that inhibited contractions. In addition, we found that these neurons and other synaptic followers of C2 received powerful inputs during feeding motor programs. In order to determine the functional significance of the synaptic outputs of C2, we studied extrinsic buccal muscles (E4 and E5) whose motor neuron (C6) is excited by C2. Extracellular recordings from these muscles indicated that they receive input during swallowing and rejection, but not during biting movements. Lesions of these muscles, or of all extrinsic muscles, did not prevent animals from feeding, but decreased feeding efficiency, that is, the amount of seaweed an animal could ingest with each swallow. The data suggest that C2 is an integrative proprioceptive cell that functions as a premotor neuron. The non-MCC synaptic outputs of C2 may reinforce the actions of the central feeding motor program. Specifically, C2 appears to aid the functioning of muscles that produce fine adjustments of the buccal mass and contribute to the efficiency of feeding behavior, rather than in producing gross movements.